Wing morphometric analysis of forensically important flesh flies (Diptera: Sarcophagidae) in Thailand - Narin Sontigun (2019)
© 2018 Elsevier B.V. Flesh flies are insects of forensic importance as the larvae associated with human remains can be used to estimate a minimum post-mortem interval (PMImin) in most cases. And, because life-history traits can vary across species, correct identification is a mandatory step before being used as evidence. Adult flesh flies are extremely similar in general appearance, which causes difficulty in species identification as it is largely based on the morphology of the male genitalia; this also makes it difficult to identify females. Currently, landmark-based geometric morphometric analysis of insect wings has proven to be a valuable tool for species identification. Herein, we applied wing morphometric analysis of 524 flesh fly specimens comprising 12 species from Thailand. The right wing of each specimen was removed, mounted on a microscope slide, photographed, and digitized using 18 landmarks. Wing shape variation among genera and species were analyzed using canonical variate analysis, while wing shape variation between sexes of each species was analyzed using discriminant function analysis. A cross-validation test was used to evaluate the reliability of classification. Results of this study demonstrate wing shape can be used to separate genera and species, and distinguish between sexes of the same species, with high reliability. Therefore, the landmark-based geometric morphometric analysis of wings is a useful additional method for species and sex discrimination of flesh flies.